Powder metallurgy at the National Physical Laboratory: Dr Bryan Roebuck has been working at the National Physical Laboratory (NPL) in the UK for nearly 45 years, and is currently an emeritus senior fellow. Bryan has spent his time at NPL studying various aspects of metallurgy, including metal powders, and has published over 300 academic papers addressing metals and alloys. Laurie Winkless spoke to Bryan to find out more about his work. Issue 2 (March 2016) - Roebuck, Bryan; Winkless, Laurie
Abstract : Metal Powder Report spoke to renowned powder metallurgist Dr Bryan Roebuck, about his career and work at the National Physical Laboratory in the UK.Dr Bryan Roebuck.